Myelin Oligodendrocyte Glycoprotein (MOG) Antibody Diseases in Children in Central South China: Clinical Features, Treatments, Influencing Factors, and Outcomes - Mao, Leilei; Yang, Lifen; Kessi, Miriam; He, Fang; Zhang, Ciliu; Wu, Liwen; Yin, Fei; Peng, Jing (Frontiers in Neurology, 2019)
Background and purpose: We analyzed the clinical manifestations of children with myelin oligodendrocyte glycoprotein (MOG)-antibody (Ab) disease in Central South China. Methods: A retrospective study of children (0–14 years old) with MOG-Ab disease in Central South China was carried out from January 2015 to October 2018. Demographics, clinical features, treatment, and outcome were reviewed. Results: Twenty-five patients with MOG-Ab disease were enrolled (onset age from 3 years to 12.4 years old; median age, 6.6 years; 13 females). The median follow-up period was 15 months (range 7-63 months). Fever (47.4%), encephalopathy (47.4%), and lesions on white matter and/or deep gray matter (52.6%) was most frequent in children under 9 years old, while opitic neuritis (ON) (66.7%), and lesions on spinal cord and/or optic (50%) was most frequent in children more than 9 years old. Till the last follow-up, 10 (40%) patients with MOG-Ab had multiphasic courses while 15 (60%) had a monophasic course, and the mean follow-up time had significant difference (10.67 to 31 months, p=0.0001). Disease-modifying drugs were used at least once in 14/25 (56%) patients with rituximab (RTX) or/and azathioprine (AZP) or mycophenolate mofetil (MMF). The annualized relapse rate before and during treatment was 2.4 (0.67-8.22) and 0 (0-3.43) (p < 0.05). The MOG-Ab titer changed to lower or negative in 6/10 children after treatment of rituximab (RTX) and remained in 3/10 children without treatment of RTX. The median Expanded Disability Status Scale of our study were 0 (range 0-2), and all pediatric patients except for one child (96%, 24/25 patients) had a full recovery. Conclusions: MOG-Ab disease of Chinese children share the same clinical characteristics with Caucasians, and a better prognosis than Caucasians. There is an age-dependent phenotypes, with brain involvement more frequently seen in younger children (<9 years) and ON and NMOSD in the older children (>9 years). Disease-modifying drugs, such as AZA, MMF or RTX, can reduce ARR.